Peningkatan keterampilan menyapaikan pendapat melalui model pembelajaran kooperatif tipe think pair and share kelas IV sekolah dasar - Rima Rismayaningsih; Rukayah Rukayah; Tri Budiharto (Didaktika Dwija Indria, 2020)
Abstract. The purpose of this study to improve skills to convey opinions using cooperative learning models think pair and share. This research is a Classroom Action Research with two cycles. The subjects of this study were the fourth grade students of SD Negeri Mangkubumen Kulon No. 83 Surakarta in the 2019/2020 school year, totaling 16 students. This study uses data collection techniques in the form is interviews, observations, tests, and documentation with data validity and triangulation data analysis. Analysis of the data used is the Miles-Huberman interactive analysis model. The first cycle produces a classic 50% percentage, and the study continues with the second cycle with a 75% percentage in classical terms. Based on the results of the study, it can be concluded that the cooperative learning model of think pair and share types can improve the skills of communicating the opinions of fourth grade students of SD Negeri Mangkubumen Kulon No. 83 Surakarta academic year 2019/2020 Learning. Keywords: Skills in Expressing Opinions, Think Pair and Share Type Cooperative Learning Models, elementary school